Medieval Cityscapes Today - Clarke, Catherine A. M. (Past imperfect (ARC Humanities Press), 2019)
This book explores medieval cityscapes within the modern urban environment, using place as a catalyst to forge connections between past and present, and investigating timely questions concerning theoretical approaches to medieval urban heritage, as well as the presentation and interpretation of that heritage for public audiences. Written by a specialist in literary and cultural history with substantial experience of multi-disciplinary research into medieval towns, Medieval Cityscapes Today teases out stories and strata of meaning from the urban landscape, bringing techniques of close reading to the material fabric of the city, as well as textual artefacts associated with it.